A critical analysis of the relevance of the South African research and development tax incentive to small and medium-sized enterprises (SMEs) and start-ups - Tau, Thato (My University, 2019)
Industries, companies, and economies; all are changing and staying still is not an option. This highlights the importance of innovation, and how it can no longer be dismissed as just another business buzzword. In the same vein, the important role that small and medium-sized enterprises (SMEs) and start-up companies play in driving innovation, job creation, economic growth, and social values cannot be ignored. One way in which governments can better nurture and support the participation of SMEs and start-ups in the promotion of innovation, thereby driving productivity, growth and job creation, is through research and development (R&D) tax incentives. There are a variety of ways in which the design of R&D tax incentives can be shaped. There is also scope to sharpen its focus by closer targeting of organisations identified as vital for society but have special needs for support. For instance, many countries who offer an R&D tax incentive either explicitly or implicitly target SMEs and start-ups who are often loss-making and for whom some incentives can be a highly-valued source of finance. This research report explores whether the South African R&D tax incentive benefits SMEs and start-up companies by comparing various design features of the South African R&D tax incentive against some other countries’ R&D tax incentives. The main findings show that although the Department of Science and Technology has gone some way to fixing the issues previously faced by the R&D tax incentive programme, there is still more that can and should be done to ensure that the incentive better meets the interests of SMEs and start-ups.
A research report submitted to the faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation)
Keywords: Business enterprises--Taxation--South Africa.; Income tax--South Africa; Small business